Lipid composition of Padina tetrastomatica (Dictyotales, Phaeophyta), a brown seaweed of the west coast of India - Narayan, Bhaskar; Miyazhita, Kazuo (Indian Journal of Fisheries, 2011)
Evaluation of the lipid class and fatty acid composition of Padina tetrastomatica harvested from the Arabian Sea (Indian Ocean) off Goa, west coast of India formed the materials of the study. Glycolipids formed the major lipid class followed by neutral- and phospholipids. Palmitic acid (C16:0) was found to be the predominant fatty acid, with saturated fatty acids contributing to the major portion of the total fatty acids. However, among the unsaturated fatty acids poly unsaturated fatty acids (PUFAs) formed the major portions and were highest in phospholipids (PL). The degree of unsaturation (DU) and mean chain length (MCL) of PUFAs are also presented